An Analysis of Eccentricity-Based Invariants for Biochemical Hypernetworks. (18th October 2021) - Rashid, Muhammad Aamer; Ahmad, Sarfraz; Siddiqui, Muhammad Kamran; Manzoor, Shazia; Dhlamini, Mlamuli
Abstract : Biological proceedings are well characterized by solid illustrations for communication networks. The framework of biological networks has to be considered together with the expansion of infectious diseases like coronavirus. Also, the graph entropies have established themselves as the information theoretic measure to evaluate the architectural information of biological networks. In this article, we examined conclusive biochemical networks like t -level hypertrees along with the corona product of hypertrees with path. We computed eccentricity-based indices for the depiction of aforementioned theoretical frameworks of biochemical networks. Furthermore, explicit depiction of the graph entropies with these indices is also measured.